Confidence as a Way to Synchronize Both the Financial and the Business Cycles - Brychko Maryna M. (Bìznes Inform, 2018)
The article is aimed at substantiating, defining and analyzing the synchronization of both the financial and the business cycles by forming an appropriate level of public confidence. The retrospective analysis of development and interconnection of financial and business cycles is carried out with attention to formation of a corresponding level of public confidence. It is substantiated that confidence is the only instrument of synchronization of both the financial and the business cycles. As a result of research of tendencies of development of financial markets of the USA, EU and Ukraine in pre-crisis, crisis and crisis periods, taking into consideration high level of financial integration and financialization of world economies, it is reasoned that financial Instability is a major factor in the erosion and crisis of public confidence. The article considers the situations of irrational behavior of economic agents as result of formation and accumulation of imbalances in the financial market and their negative consequences for economic security of the country. It is proved that confidence is a procyclical indicator that determines the cycle of economic development with a certain time lag. With a view to the turmoil in the financial market forming the corresponding cyclical fluctuations of public confidence, the necessity of research of business cycle through the prism of public confidence (established in accordance with the financial cycle), but with lagging in terms of synchronization, is substantiated.